2018
DOI: 10.1136/jim-2017-000468
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 Levels are Related to Insulin Resistance and Carotid Atherosclerosis in Subjects with Familial Combined Hyperlipidemia

Abstract: Familial combined hyperlipidemia (FCH) is a primary atherogenic dyslipidemia with insulin resistance and increased cardiovascular risk. Plasminogen activator inhibitor type 1 (PAI-1) and myeloperoxidase (MPO) activity are associated with proinflammatory and atherothrombotic risk. Our aim was to study the role played by PAI-1 and MPO activity in the carotid atherosclerosis prevalence in FCH subjects. 36 FCH unrelated subjects (17 women) were matched by age and body weight with 36 healthy normolipidemic subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Furthermore, studies on the effects of pharmacological PAI-1 inhibition on atherogenesis in mice with obesity and metabolic syndrome also suggested a role for PAI-1 in adipose tissue inflammation, macrophage accumulation, and inducing senescence of smooth muscle cells through its interaction with LRP1 [ 49 ]. Whereas several studies demonstrated substantial evidence for PAI-1 as an independent risk factor for CVD including myocardial infarction and stroke [ 50 , 51 , 52 ], coronary heart disease [ 53 ], venous thrombosis [ 54 ], and atherosclerosis [ 45 , 55 ], other studies could not confirm these associations or the significance for the link was lost after adjusting for other risk factors, such as age, sex, and metabolic abnormities [ 52 , 56 , 57 , 58 ].…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…Furthermore, studies on the effects of pharmacological PAI-1 inhibition on atherogenesis in mice with obesity and metabolic syndrome also suggested a role for PAI-1 in adipose tissue inflammation, macrophage accumulation, and inducing senescence of smooth muscle cells through its interaction with LRP1 [ 49 ]. Whereas several studies demonstrated substantial evidence for PAI-1 as an independent risk factor for CVD including myocardial infarction and stroke [ 50 , 51 , 52 ], coronary heart disease [ 53 ], venous thrombosis [ 54 ], and atherosclerosis [ 45 , 55 ], other studies could not confirm these associations or the significance for the link was lost after adjusting for other risk factors, such as age, sex, and metabolic abnormities [ 52 , 56 , 57 , 58 ].…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…The PAI-1 is a highly responsive/induced adipokine by pro-inflammatory cytokines and ROS, especially cytokines related to VAT and hepatic ectopic fat such as TNF-α, transforming growth factorbeta (TGF-β) and insulin [82]. Strongly connected to MetS pathophysiology, it has become an important biomarker to evaluate the syndrome severity due to its association with IR, non-alcoholic fatty liver disease, a proinflammatory and prothrombotic state [83,84]. The major pathogenic contribution of PAI-1 to the MetS' risk factors cluster is linked to the establishment of a prothrombotic state as found in patients with elevated circulating levels of this cytokine.…”
Section: Pathophysiologymentioning
confidence: 99%
“…It complements the activities of protein anticoagulants and endothelial-derived platelet inhibitors, such as proteins C, S, anti-thrombin III, and nitric oxide [5]. It is an endogenous defense mechanism for the prevention of atherosclerotic change, and there are some reports that the tPAI-1 levels are positively and independently associated with the degree of IMT [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…tPAI-1 is known to be associated with a proin ammatory atherosclerotic risk. Moreover, there are reports that tPAI-1 is independently associated with the degree of intima media thickness (IMT) [6,7]. Thrombomodulin (TM) has an anticoagulant effect that is stimulated by activating protein C, and this is corroborated by reports about elevated blood levels of TM in patients with acute pulmonary embolism [8,9].…”
Section: Introductionmentioning
confidence: 98%